(untitled) (Research, Society and Development, 2022)
Bone loss is a multifactorial phenomenon that can make rehabilitative treatment unfeasible in edentulous patients. Among the available treatment modalities is the use of autogenous graft. The aim of the present study is to evaluate, through a literature review, the amount of vertical and horizontal bone gain promoted using autogenous bone grafts en bloc using the SBB technique when compared with inlay-type bone grafts. In this literature review, a search was performed in the main health databases PUBMED and LILACS, looking for articles published in English in the last 15 years. After reading titles and abstracts, only 4 articles were considered eligible for full text reading. The final studies included were published between 2009 and 2020, both being retrospective cohort studies. The aspects evaluated in both articles were vertical and/or horizontal bone gain using the Khoury technique and the Inlay technique. Among the 4 studies included, 2 relate to the Khoury technique and the mean vertical and horizontal bone gain respectively were 3.2mm and 5.2mm and two other articles described the Inlay technique which resulted in 4.9mm and 6.67mm. From this literature review, we can conclude that the Inlay technique presents better results in horizontal bone gain, but when three-dimensional bone gain is desired, the Khoury technique is more effective.